Pb(II) and Cd(II) removal from aqueous solution, shipyard wastewater, and landfill leachate by modified Rhizopus oryzae biomass. (5th April 2018) - Naeimi, Behrouz; Foroutan, Rauf; Ahmadi, Bahram; Sadeghzadeh, Farzaneh; Ramavandi, Bahman
Abstract: This study was designed to remove Pb(II) and Cd(II) from aqueous solution, shipyard wastewater, and sanitary landfill leachate using an alkaline-modified Rhizopus oryzae biomass. According to the Fourier transform infrared test, different functional groups like O–H, N–H, C=O, and P–O were detected in the bioadsorbent. The x-ray fluorescence (XRF) analysis showed that CaO, P2 O3, and SO3 oxides have the highest content in the bioadsorbent. The surface area of modified Rhizopus oryzae was obtained as 20.32 m 2 g −1 . The effect of initial pH, temperature, contact time, and bioadsorbent dose on the metals removal was discussed. At optimal conditions, maximum Pb(II) and Cd(II) removal was obtained 95.66% and 94.55%, respectively. Freundlich model was well- accurately described the equilibrium data. Among four studied models, the pseudo-second-order was better able to describe the kinetic behavior of the bioadsorption process. The amount of enthalpy, free energy of Gibbs, and entropy parameters indicated that the bioadsorption process of studied heavy metals is negative, exothermic, and spontaneous. The amount of heavy metals in a shipyard wastewater and sanitary landfill leachate was significantly decreased by using the developed bioadsorbent.